Implementation of Islamic Religious Education Learning in the Independent Curriculum Using the Jigsaw Method to Enhance Student Activeness at SMAN 1 Kutorejo - Alfiyah Ayu Qomariyah; Fina Surya Anggraini (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study aims to determine the implementation of Islamic religious education learning curriculum independence with the jigsaw method in increasing student activity in class X SMAN 1 Kutorejo, and to determine the implications of student activity in Islamic religious education learning with the jigsaw method in class X SMAN 1 Kutorejo.This study uses a qualitative method using a case study. This study will focus on the implementation of Islamic religious education learning curriculum independence with the jigsaw method in increasing student activity in class X SMAN 1 Kutorejo. For data collection using interview, observation and documentation techniques. Furthermore, for data analysis used by researchers, namely data reduction, data presentation and data verification. While for the data validity test technique, researchers use source triangulation. The results of this study indicate that the jigsaw method planning process prepares learning outcomes, learning objectives, learning objective flow, learning plans and selects materials along with making questions. The implementation of the jigsaw method, educators explain the steps for implementing jigsaw learning, explain the material from educators and form groups randomly with 4-5 students from each group. Educators provide different questions but one material, then educators give time to discuss the original group to complete the answers to the questions, then after finishing discussing with the original group, educators instruct to gather with the expert group to find out the results of the discussion with the original group. Achieving the results of the discussion then concluding the material. Although in its implementation it has been successful, it has not been optimal because there are students who have not been able to play a good role. For the evaluation stage, it is seen the activeness of discussing with the group, presentations from the results of group discussions, work results and conducting written or oral tests. The impact after implementing the jigsaw method is that students' understanding of the material increases, social skills increase, motivation and participation increases, communication skills develop, and academic anxiety decreases